FROM STEAM TECHNOLOGY IN PRESCHOOL ORGANIZATIONS EFFECTIVE METHODS OF USE (Web of Teachers: Inderscience Research, 2024)
This article explores effective ways to incorporate STEAM (science, technology, engineering, arts, and mathematics) technology into preschool organizations. It discusses the benefits of integration with STEAMerta in childhood education, provides practical implementation strategies, presents successful implementation outcomes, and provides insights into the future of steam preschool education.